THE PROBLEMS OF PERFORMANCE MONITORING TO TAKLE THE TASKS OF THE AIRCRAFT CONTINUED AIRWORTHINESS - Yu. M. Chinyuchin (Научный вестник МГТУ ГА)
Improving of the aircraft continued airworthiness system is currently becoming of particular importance applied both to aircraft of domestic and foreign production, used in civil aviation of Russia. This article discusses the background and content of the tasks for long-haul aircraft continued airworthiness, which presents a challenge directly related to the provision of intensive, regular, economically viable, and safe operation of assigned airline fleet. A special place among the problems of continued airworthiness is held by the creation and organization of mechanisms and methods of resource status and age of the assigned airline fleet monitoring to manage its forecasting and timely updates. Not least important among the issues of resource and age structure monitoring to be considered is the need to improve the design of aircraft, taking into account preliminary technical and economic feasibility assessment of its modifications in the interests of the operator. A deep study of the contents of the monitoring allows to develop up-to-date methodological and scientific basis for building an integrated system of aircraft resource management and timing services. This system is developed based on the integrated approach that allows to provide a solution to the entire set of problems presented in this article and faced by professionals and scientists involved in the aircraft maintenance programs development on the stages of their design and manufacturing and long operation of aircraft continued airworthiness.